DESIGNING AN ONLINE BUS TICKET BOOKING INFORMATION SYSTEM (E-TICKETING) APPLICATION ON PO. HANDOYO: PERANCANGAN APLIKASI SISTEM INFORMASI PEMESANAN TIKET BUS ONLINE (E-TICKETING) PADA PO. HANDOYO - Primagita Fridhayanti; Ludfi djajanto; Zainal Abdul Haris (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
Online application design as a form of manual system changes to an application that is easily accessible by all parties. An information system is a particular way of providing the information needed by an organization to operate in a successful manner and for a business organization in a profitable way. To improve the ability of human resources to use increasingly sophisticated technology with the help of application-based e-ticketing so as to minimize missed procedures and incorrect procedures. This study is a Research and Development (R&D) research using five stages, namely analyze (analysis), design (design), development (development), implementation (application) and evaluation (evaluation) (ADDIE). The solution to solving the problem that can be done is to hold discussions or communication between the organizers of the Handoyo Bus and prospective users of the Handoyo Bus Web Apps either directly or through remote communication media, so that both parties can synchronize information and then can find out where the error is from the problem. Furthermore, socialization for Handoyo Bus employees for the use of Web Apps is carried out regularly so that prospective passengers can be directed to make ticket reservations through web apps, thereby reducing ticket sales queues and making it easier for the finance department to book cash inflows and cash outflows